Implementasi Kebijakan Pengangkatan Pejabat Struktural Di Lingkungan Pemerintah Kota Ternate ( Suatu Studi di Badan Kepegawaian Daerah Kota Ternate ) - Samad, Muhajir; Lengkong, Florence Daicy; Dengo, Salmin (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : This research aims to know how policy implementation appointing structural officials onthe government Ternate Regional Personnel Board in particular. This research uses qualitativeresearch. Informant or was as many as 10 people officials/staffs in Regional Personnel Board,namely: the head of the body (1), the chief (2), the heads of sub division (2), and the head of subsection(2), and the staff/executive (3 persons). Technical data collection is an interview. Dataanalysis done by analysis techniques qualitative analysis interactive model of Miles andHubernann. Results of research shows: (1) seen from dimensions policy implementation modelEdward III (communication, resources, this appointment, and the structure) policy implementationappointing structural generally it is good but has not yet, there is still a weakness. (2) processadoption (selection and the determination) structural generally it is good, but they have not beenseen in optimum objectivity; not all structural officials that are to meet all the conditions page infull for the structural positions as stipulated in certain pp.no.13 in 2002.Keywords : policy implementation, the appointment structural